The Perception Of Medical Students In Clinical Years Towards Bedside Teaching In Universiti Malaysia Sarawak (UNIMAS) - Nur Amir, Luqman Roslan; Tang, Betty Jin Jin; Noor Syafawani, Bohan; Hashveena, Veerakumar; Siti Maryam, Ahmad Kendong; Saiful Bahri, Talip (Institute of Borneo Studies, UNIMAS, 2016)
This study was done to survey on the different perceptions among medical students toward bedside teaching that includes both the pros and cons of this type of learning method. A 130 clinical year students (Year 3, Year 4, Year 5) from Faculty of Medicine and Health Science (FHMS) of Universiti Malaysia Sarawak (UNIMAS) participated in this study. Questionnaires consisted of three different sections were distributed and the collected data were analyzed using Analysis of Variance (ANOVA) test. From the study, it was found that, clinical year students had perceived differently regarding the bedside teaching mainly on three aspects. These includes the care given by students to their patients, the increased risk of exposure to diseases, and more than 1 lecturer per group during teaching (P<0.05). Majority of the students agreed that bedside teaching is the most straight forward method to convey knowledge, promoting better understanding, encouraging active learning, developing better clinical skills and nurturing crucial ethical aspects. Students also agreed that bedside teaching in UNIMAS can be improved by respecting confidentiality of patients, summarising each discussion session, encouraging feedback and using simple terms during teaching session,. As conclusion, from this study, it was found that there were a few different in the perceptions toward bedside teaching between clinical year students of UNIMAS.